Evaluation of the Achievements of the XX Papua PON in Central Java First Excellence Martial Sports Branch - Abdul Ghoni; Taufiq Hidayah; Fajar Awang Irawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The development of the achievements of the leading martial arts sports in Central Java is a place in the achievements of the XX PON in Papua. The purpose of this research is to evaluate the antecedents, transactions and outcomes of the first branch of the Central Java Martial Arts sport. The data sources in this study are administrators, coaches, athletes and related stakeholders. Data collection techniques are observation, interviews, documentation. The data obtained were analyzed as follows: data collection, data reduction, data presentation, drawing conclusions. The results of this study, the athlete development program for the Central Java First Martial Arts Branch has been running well and is structured according to the background, vision, mission and objectives of the coaching program that has been made. Recruitment of coaches and athletes has gone well, because they meet the conditions, the training program has been running according to the scheduled training program but not optimal, the facilities and infrastructure are not good, some of the training equipment is not standard at the training ground, the funding is still not good welfare is not good and not optimal in meeting the needs of coaches and athletes. Not good, because it is not stable in achieving achievements every year. In conclusion, the achievements of the Central Java I Preferred Martial Arts Branch in less than the last 3 (three) PON starting from the year were still not optimal in obtaining an achievement in each sport, regional, national and international championships.